Sensitivity Analysis of Vibrating Laminated Composite Rec-tangular Plates in Interaction with Inviscid Fluid Using EFAST Method - Korosh Khorshidi; Moein Taheri; Mohsen Ghasemi (Mechanics of Advanced Composite Structures)
This work investigates the sensitivity analysis of vibrating laminated composite rectangular plates in interaction with inviscid fluid using the modified higher-order shear deformation plate theory. The EFAST method which is based on variance and is independent of any assumption of linearity and uniformity between inputs and outputs is utilized for sensitivity analysis of laminated composite rectangular plates. Theoretical formulations, both for the laminated rectangular plates in interaction with inviscid, incompressible and irrotational fluid and the sensitivity analysis technique are summarized here. A Cartesian coordinate system is used to describe governing equations of fluid-structure interaction. Hamilton's variational principle is used to derive the Eigen problem of the complex system. A numerical investigation is carried out by using the Galerkin method and the boundary conditions of the plate are simply supported. A set of admissible displacement functions which satisfy identically the geometric boundary conditions are used to calculate the wet natural frequencies of the plate. In the numerical examples, the effect of the aspect ratio, thickness ratio and material orthotropy orientation of the plate, depth ratio and width of the fluid on the fundamental natural frequency of the vibrating laminated composite rectangular plates are examined and discussed.